The Implementation of Agile Organization at the Regional Development Planning Agency of Depok City, West Java Province - Ruhana, Faria (GoAcademica Research & Publishing, 2024)
The concept of an agile organization is essential in Indonesian governance to foster adaptive, responsive, and integrated bureaucracies capable of addressing rapid changes, especially in the digital era and during crises. At the Regional Development Planning Agency (Bappeda) of Depok City, challenges remain in implementing an agile organization effectively. This study employs a Convergent Parallel Mixed Methods approach, utilizing questionnaires, interviews, observations, and documentation for data collection. Quantitative data were analyzed using descriptive statistics, complemented by qualitative analysis through data reduction, data presentation, and conclusion drawing. The findings reveal that while the organization demonstrates a commitment to customer satisfaction, further improvements are necessary. Leadership empowerment has been effectively implemented but lacks uniformity across the organization. Adaptive and flexible processes are in place, though their application is inconsistent and suboptimal. Continuous improvement practices are evident, but challenges persist in ensuring consistency and team involvement across departments. Transparency is generally established, yet certain teams face difficulties achieving comprehensive openness. These findings highlight the need for strategic enhancements to optimize the implementation of agile organizational principles.